Prevalence of Learning Disability and Emotional Problems among Children: An Overview of Emotion and Creativity Focused Interventions - MPhil , Nayana Mariya Kuriyan; K, Jayasankara Reddy; James, Justine K (International Journal of Psychosocial Rehabilitation, 2018)
Learning disability (LD) among school going children affects their academic and social life. Children with LD struggle in their learning process. Delay in identification and inadequate remedial and emotional support derail their overall development. In India, school based psychological assessment and services are at infancy stage. Teachers are not equipped to meet the special needs of such children. This review article aims to describe the prevalence of LD and the psychological issues faced by the children with LD. This article also gives an over- view of interventions provided to children with LD. The article is based on a systematic review of available lit- erature, published in peer reviewed and indexed journals during 2000-2017. Articles for review were identified from following data base; EBSCO, PUBMED, PROQUEST, JSTOR, SAGE, TAYLOR AND FRANCIS and GOOGLE SCHOLAR. Based on selection criteria, 56 articles were considered for systematic review. Findings indicate that the Prevalence of LD in India has been identified as 1% to 19% among school going children. Re- view of the prevalence articles reported the mean of prevalence as 10%. Children with learning disability are vulnerable to low self-esteem, anxiety and depression. Though few intervention packages are developed for re- medial training and to enhance the skills and self-esteem, those programmes are not used appropriately in India. Children with LD need more focused and specialized care and nurturing exposure to ensure their emotional growth and wellbeing.